Vulvar involvement in autoimmune bullous diseases. - Marren, P; Wojnarowska, F; Venning, V; Wilson, C; Nayar, M (1993)
The autoimmune blistering diseases are characterized by involvement of the skin and mucous membranes. On mucosal surfaces, although the initial lesion is often a blister, friction results in erosions. We report on 140 female patients with a variety of blistering diseases examined in the bullous disease clinic. Vulval involvement was found in 5 of 55 adult patients and in 2 of 3 girls with bullous pemphigoid. Sexual abuse was initially suspected in one child. Twenty-six women had cicatricial pemphigoid; of these, 14 had vulval involvement, often with severe scarring. Chronic bullous disease of childhood was identified in 20 girls; perineal involvement was present in 16 causing initial misdiagnosis of herpes simplex in one case and sexual abuse in another. Vulval involvement was less frequent in linear IgA disease (the adult counterpart of chronic bullous disease of childhood), occurring in 9 of 22 patients. One of two adults and two of three girls with epidermolysis bullosa acquisita had vulval involvement. Finally, of nine female patients with pemphigus, four had vulval involvement, all of whom had pemphigus vulgaris. Blistering diseases are rare, but vulval involvement is common across the spectrum of these diseases. When mucosal involvement predominates, diagnostic difficulties can arise.